Digestibility and metabolizable energy of some carbohydrate sources for dogs - Fortes, C. M. L. S.; Carciofi, A. C. [UNESP]; Sakomura, N. K. [UNESP]; Kawauchi, I. M.; Vasconcellos, R. S. (Elsevier B.V., 2010)
A digestibility study was conducted to determine the nutritional value of broken rice, high oil maize, millet, sorghum, maize germ, rice bran and wheat bran as ingredients for dog foods. Eight adult dogs were housed in metabolic cages, and distributed into 8 x 8 Latin square experimental design, with eight diets and eight replicates per diet. The difference, or substitution method was used to estimate ingredient digestibility. A reference diet was formulated based on nutritional requirements of dogs. For each test diet, 300 g/kg of the reference diet was replaced with the ingredient evaluated. All the diets were extruded. The total tract apparent nutrient digestibility for high oil maize, sorghum, millet, broken rice, maize germ, wheat bran and rice bran were, respectively: 0.893, 0.905, 0.859, 0.905, 0.654, 0.593 and 0.550 for dry matter; 0.884, 0.884, 0.803, 0.753, 0.656, 0.682 and 0.729 for crude protein; 0.855, 0.786, 0.821, 0.668, 0.482, 0.538 and 0.852 for fat; 0.503, 0.741, 0.668, 0.744, 0.232, 0.209 and 0.129 for dietary fiber: and 0.986, 0.987, 0.991, 0.992, 0.955, 0.896 and 0.904 for starch. The metabolizable energy (MJ/kg, as-fed basis) was 14.4, 13.1, 13.5, 13.1, 9.1, 9.0 and 12.0, respectively. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Dog food; Cereals; Fiber; nutrient digestibility; Starch; Ingredient